Развитие как цель : телеологическое толкование международных договоров в практике международного центра по урегулированию инвестиционных споров - Якубовская, Наталья Алексеевна; Якубовська, Наталія Олексіївна; Jakubovskaja, Natal'ja (My University, 2013)
The practice of international courts in relation to interpretation of the international treaties, which regulate interstate cooperation in the field of development, in the light of object and purpose is analyzed. As an example, the practice of International Centre for Settlement of Investment Disputes is given. It is shown that a teleological interpretation of the 1965 Convention on the Settlement of Investment Disputes between States and Nationals of Other States and the number of international investment agreements has allowed the investment tribunals to conclude that foreign investments should positively contribute to economic development of states.
Якубовская Н. А. Развитие как цель : телеологическое толкование международных договоров в практике международного центра по урегулированию инвестиционных споров / Н. А. Якубовская // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 333-341.
Keywords: развитие; телеологическое толкование международного договора; МЦУИС; иностранные инвестиции; ртозвиток; телеологічне тлумачення міжнародного договору; МЦВІС; іноземні інвестиції; development; teleological interpretation of international treaty; ICSID; international investments